ONLINE SELLER FOR A MONTH (OSFAM) DAN IMPLEMENTASINYA TERHADAP PENGABDIAN MASYARAKAT SEBAGAI MEDIA AJAR - Handayani, Dian (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract— The 4.0 industrial revolution that carries the internet of things provides convenience in various aspects of life including shopping. Trading with online systems or e-commerce is increasingly prevalent. Platforms devoted to shopping online have mushroomed. Students must be prepared to face fierce competition in the world of entrepreneurship. On the other hand, students must also continue to be fostered by social life and empathy. Online Seller for a Month is a design of learning activities that aims to prepare students in the world of entrepreneurship based on technology in order to be able to face the challenges of the industrial revolution 4.0 and at the same time be trained to be able to participate in public service. Keywords— online shopping, e-commerce, public service Abstrak— Revolusi industri 4.0 yang mengusung internet of things memberikan kemudahan dalam berbagai aspek kehidupan termasuk berbelanja. Perdagangan dengan sistem online atau e-commerce semakin marak dilakukan. Platform yang dikhususkan untuk berbelanja online telah menjamur. Pelajar harus siap untuk menghadapi persaingan ketat di dunia kewirausahaan. Dilain sisi, pelajar juga harus terus dipupuk jiwa sosial dan empatinya. Online Seller for a Month merupakan sebuah rancangan kegiatan pembelajaran yang bertujuan untuk mempersiapkan peserta didik dalam dunia kewirausahaan berbasis teknologi agar dapat menghadapi tantangan revolusi industri 4.0 sekaligus dilatih untuk dapat ikut serta dalam pengabdian masyarakat. Kata Kunci— berbelanja online, e-commerce, pengabdian masyarakat